Morfologia e morfometria dos tipos de fibras do músculo reto abdominal de cadelas (canis familiaris) durante a gestação - de Brito, Maila Karina Mattos [UNESP]; Carvalho Junior, Colombo Guerra; dal Pai, Alexandre; dal Pai, Vitalino; Giacometti, José Alberto [UNESP] (My University, 2007)
The present paper deals with the evaluation of morphological and morphometric alterations of slow-twist (I) and fast-twitch (II) fibers of rectus abdominis muscle of adult female dog during pregestational phase, at 30 and 60 days of pregnancy and at 30 days after the parturition. At the every phases, using the open biopsy technique, muscle samples were collected. The samples were plunged. Histological sections were cut in a microtome. For general morphology, some sections were stained with HE. Subsequent sections were reacted for myofibrillar ATPase (m-ATPase), after alkaline (pH 10.4) and acid (pH 4.4) pre-incubations, in order to identificate type I and II fibers. In the pre-gestational phase, muscle tissue revealed to be composed by fibers with different diameters, presenting polygonal outlines and one or more periphery nuclei. At 30 days of pregnancy, muscle fiber characteristics were similar. At 60 days, in addition to the existence of normal fibers, polymorphic and small diameter fibers were frequent. At 30 days after the parturation, the morphology of muscle fiber were similar to that observed in the pre-gestational phase. In the four phases, type II fiber diameters were lager than type I. The diameters of both fiber types showed a significant reduction in the 30 days phase and a significative increasing at 60 days. The expansion of the abdominal wall during the pregnancy represents a chronic stimulus, induced changes in the morphology and in the fiber type diameters.
Morphologic and morphometry of rectus abdominis muscle fiber types of the during the gestation dog (canis familiaris)
Keywords: Female dog; Fiber type i and ii; Gestation; Morphometry; Retus abdominis muscle; Canis familiaris